F.01 Prognostic factors in adults with spinal cord injury without radiological abnormalities (SCIWORA): MRI study. (17th June 2016) - Martinez-Perez, R; Paredes, I; Cotrina, J; Pandey, S; Lagares, A
Abstract : Background: Spinal Cord Injury Without Radiological Abnormality (SCIWORA) is underreported and poorly recognized in adults. This entity is an important subtype of spinal cord injury (SCI) with relatively good outcomes. Despite this, few studies have been performed to determine specific imaging-related prognostic factors.Methods: A retrospective review of adult patients with cervical SCI admitted to two University hospitals from January 2000 to December 2010 was performed. Only patients with an MRI performed within 72 hours after trauma were included. All patients with bony injury or traumatic malalignment were excluded. Data gathered on the remaining patients included demographics, mechanism of injury, severity of SCI, long-term patient outcome, improvement in neurological condition and MRI results.Results: 49 patients selected. Patients with extramedullary hemorrhage showed worse neurological status at initial examination. Disruption of either the anterior longitudinal ligament or ligamentum flavum was associated with worse outcomes at initial examination and at 1-year follow up. Lesion length was also significantly associated with outcomes at 1 year evaluation and initial evaluation.Conclusions: Early MRI has an important prognostic value in patients suffering SCIWORA. Lesion length is a powerful predictor of outcome. Soft tissue injury and spinal cord changes play a role in the severity of injury as well as the ability to recover.